Wearable Electronic Textiles from Nanostructured Piezoelectric Fibers. Issue 4 (16th February 2020) - Mokhtari, Fatemeh; Spinks, Geoffrey M.; Fay, Cormac; Cheng, Zhenxiang; Raad, Raad; Xi, Jiangtao; Foroughi, Javad
Abstract: Wearable energy harvesting is of practical interest for many years and for diverse applications, including development of self‐powered wireless sensors within garments for human health monitoring. Herein, a novel approach is reported to create wearable energy generators and sensors using nanostructured hybrid piezoelectric fibers and exploiting the enormous variety of textile architectures. It is found that high performance hybrid piezofiber is obtained using a barium titanate (BT) nanoparticle and poly(vinylidene fluoride) (PVDF) with a mass ratio of 1:10. These fibers are knitted to form a wearable energy generator that produced a maximum voltage output of 4 V and a power density 87 μW cm −3 which is 45 times higher than earlier reported for piezoelectric textiles. The wearable energy generator charged a 10 μF capacitor in 20 s which is four and six times faster than previously reported for PVDF/BT and PVDF energy generators, respectively. It also emerges that the established knitted energy harvester exhibits sensitivity of 6.3 times higher in compare with the piezofibers energy generator. A knee sleeve prototype based on a PVDF/BT wearable device for monitoring real‐time precise healthcare is demonstrated. The developed processing method is scalable for the fabrication of industrial quantities of smart textiles. Abstract : A novel approach is reported to create wearable energy generators and sensors using nanostructured hybrid piezoelectric fibers and exploiting the enormous variety of textile architectures. A knee sleeve prototype based on a nanostructured piezoelectric wearable device for monitoring real‐time precise healthcare is demonstrated.